2016
DOI: 10.1038/srep30920
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation in a non-heterocystous cyanobacterial mat from a mountain river

Abstract: In situ nitrogen fixation was investigated in a cyanobacterial mat growing on the bed of rocks of the Muga River, Spain. The filamentous non-heterocystous cyanobacterium Schizothrix dominated the mat, showing nitrogenase activity in the light at similar rates to those found in nearby heterocystous Rivularia colonies. N2 fixation in the light was significantly increased by an inhibitor of PSII and oxygen evolution, DCMU (3-[3,4-dichlorophenyl]-1,1-dimethylurea), and anaerobic conditions. However, no nitrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 67 publications
0
29
0
1
Order By: Relevance
“…On the other hand, the significant increase in bioavailable N in May appeared to be related to late season rains (in April) indicative of the investment in the storage of N in cyanophycin (granules) and EPS. Other records of seasonal influence on both C and N fixation have been previously demonstrated; however, the synchrony between these events on a monthly and bimonthly basis shows how well balanced the cyanobacterial biophysical and chemical functions were, dictated by rainfall and consequently soil moisture (Büdel et al, 2009;Castillo-Monroy et al, 2010).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…On the other hand, the significant increase in bioavailable N in May appeared to be related to late season rains (in April) indicative of the investment in the storage of N in cyanophycin (granules) and EPS. Other records of seasonal influence on both C and N fixation have been previously demonstrated; however, the synchrony between these events on a monthly and bimonthly basis shows how well balanced the cyanobacterial biophysical and chemical functions were, dictated by rainfall and consequently soil moisture (Büdel et al, 2009;Castillo-Monroy et al, 2010).…”
Section: Discussionmentioning
confidence: 77%
“…It is now understood that there is a broad range of N-rich metabolites that are continually released and consumed by Microcoleus (Baran et al, 2015). It has also been demonstrated that N enrichment was associated with Gloeocapsa (Wyatt and Silvey, 1969), Porphyrosiphon (Prasanna et al, 2000) and Schizothrix (Berrendero et al, 2016). Indeed, many cyanobacteria obtain N by scavenging from mutually shared EPS (Rossi et al, 2017) or have multiple mechanisms for N fixation either in the dark (Lüttge, 1997), through O 2 inhibition (Stal, 1995), in anaerobic circumstances (Murukesan et al, 2016) or aquatic cyanobacterial mats when submerged under water (Berrendero et al, 2016;Stewart, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of strains to fix nitrogen and produce cyanide seems to be not strictly related with heterocyte formation, as nifH gene fragment was also present in non-heterocytous cyanobacteria strains that produce nitrogen. Non-heterocytous cyanobacteria can fix nitrogen either in dark (Bergman et al, 2006) or in light combined with mechanisms for protecting the O 2 -labile nitrogenase (Berrendero et al, 2016). HCN can inhibit a wide range of metabolic processes (Knowles and Bunch, 1986), but the most pertinent effect in photosynthetic micro-organisms seems to be the inhibition of the reduced form of nitrate reductase (Lorimer et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In nutrient‐depleted environments, cyanobacteria are generally also considered as the principal diazotrophs. However, the magnitude and importance of this fixation in lotic ecosystems are poorly understood (Berrendero et al, ).…”
Section: Discussionmentioning
confidence: 99%